CD200/CD200R Paired Potent Inhibitory Molecules Regulating Immune and Inflammatory Responses; Part II : CD 200/CD200R Potential Clinical Applications - Drahomíra Holmannová; Martina Koláčková; Kateřina Kondělková; Pavel Kuneš; Jan Krejsek; Ctirad Andrýs (Acta Medica, 2012)
CD200 and its receptor were recognized as having the multiple immunoregulatory functions. Their immunoregulatory, suppressive, and tolerogenic potentials could be very effectively exploited in the treatment of many diseases, e.g. Alzheimer disease, rheumatoid arthritis, and allergy to name only some. Many research projects are aimed to develop clinically valuable methods being based on the structure and function of these paired molecules. In this review, we would like to introduce CD200/CD200R functions in a clinical context.